EVALUASI VALUE GOVERNANCE, PORTFOLIO MANAGEMENT, DAN INVESTMENT MANAGEMENT DALAM RANGKA PERENCANAAN INVESTASI TEKNOLOGI INFORMASI: STUDI PADA UNIVERSITAS INDRAPRASTA PGRI (UNINDRA) - Aswin Fitriansyah (LPPM, 2011)
There are several frameworks that can be used to calculate the investment value prediction. One of the frameworks used in this theses discussion is Val IT. Val IT can be used to give a clear explanation about the advantages of information technology investment in an organization. Val IT published by Information Technology Governance Institute (ITGI). Val IT consists of 3 main processes to measure the information technology value; there are Value Governance, Portfolio Management, and Investment Management. Each main process divided into several processes. Value Governance consists of 11 processes, Portfolio Management consists of 14 processes, and Investment Management consists of 15 processes. Just like an enterprise, Indraprasta PGRI University as an institution expects to have maximum result and advantage in its information technology investment planning. On the other side, Indraprasta PGRI University which have just established in 2004 and previously was the union of the STKIP PGRI Jakarta must be able to envision the information technology investment as something which can be conducted. This research conducted by identifying all Val IT process in Indraprasta PGRI University using questionnaire. Details of the questionnaire results it is concluded to implement the appropriate proposals, then these processes are classified based on characteristics of the portfolio of the organization by using the McFarlan grid's. The results of McFarlan classification is applied to determine which proposals should be in the portfolio process to be developed, held, or eliminated. This will be used by management in the investment planning to obtain business value in accordance with the organization's strategic objectives. Keywords: Information Technology Investment Planning, Val IT Framework, Value Governance, Portfolio Management, Investment Management, McFarlan grid’s, business value.